Investigation of the radiation hardness of GaAs:Cr semiconductor detectors irradiated with fast neutrons at the reactor IBR-2. (December 2020) - Kruchonak, U; Abou El-Azm, S; Bulavin, M; Chelkov, G; Gostkin, M; Guskov, A; Sheremetyeva, A; Zamiatin, N; Zhemchugov, A
Abstract: Investigation of the semiconductor detectors properties under neutron irradiation is very important for their practical application. High-resistivity gallium arsenide detectors (GaAs:Cr) were irradiated with various fast neutron fluences in range from 3.9×10 n cm −2 to 3.7×10 16 cm −2 at the IBR-2 reactor, FLNP, JINR. The neutron fluence was measured by placing silicon planar detectors at the measured points and measuring the 1 MeV (Si) equivalent fast neutron fluence. The charge collection efficiency and the current-voltage characteristics of irradiated detectors were measured, and their degradation after neutron irradiation was compared with the results obtained by irradiation with 21 MeV electrons.